2015
DOI: 10.1007/s00703-015-0386-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of southwest monsoon onset over Myanmar

Abstract: The aim of this paper was to characterize the southwest monsoon onset over Myanmar based on the model. The Regional Climate Model (RegCM3) was run for a period of 10 years (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Due to the monsoon process, the summer monsoon season in Myanmar Coast can be divided into three phases: onset phase (May), peak phase (June–August), and withdrawal phase (September–October) (Wang et al, 2014; Vergopolan et al, 2020). Thus, the results are agree with the findings of previous studies that reported higher precipitation in the months of June, July and August over Myanmar (Mie Sein et al ., 2015, 2021b; Shahzaman et al ., 2021b). On the other hand, the months of May (onset phase), September and October (withdrawal phase) reveal less precipitation in the range of 90 mm to 755 mm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the monsoon process, the summer monsoon season in Myanmar Coast can be divided into three phases: onset phase (May), peak phase (June–August), and withdrawal phase (September–October) (Wang et al, 2014; Vergopolan et al, 2020). Thus, the results are agree with the findings of previous studies that reported higher precipitation in the months of June, July and August over Myanmar (Mie Sein et al ., 2015, 2021b; Shahzaman et al ., 2021b). On the other hand, the months of May (onset phase), September and October (withdrawal phase) reveal less precipitation in the range of 90 mm to 755 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The region can be subdivided into three sub‐regions: namely, the Western fold belt (Western Ranges) in the West, the Central lowland in the middle, and the Shan‐Tanintharyi Block (the Eastern Highland) in the East (Kreft et al ., 2017; Oo et al ., 2020; Mie Sein et al ., 2021a). The climate is characteristically unstable due to steep slopes, unstable geology, and intense monsoon rains, especially mountainous areas, which are the most disaster‐prone regions (Mie Sein et al ., 2015). The country receives a large amount of precipitation in summer monsoon season, accounting for 90% of the country's total precipitation (Sein and Zhi, 2016; Ren et al ., 2017).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…This has become a common method for investigating the spatial characteristics of climatological elds. The EOFs are the eigenvectors of the covariance matrix deduced from the data eld's time series (Mie Sein et al, 2015). The time series associated with the rst two EOFs (PCs) are investigated concerning the temporal variability.…”
Section: Methodsmentioning
confidence: 99%
“…It may be one of the primary and essential factors affecting South and East Asia's climate . According to Azad et al (2022); Dubache et al (2019); Mie Sein et al (2015) crop productivity, hydropower output, foliage, water management, and biodiversity of these sections are impacted by the intensity and length of the monsoonal rains. Additionally, "India's inter-annual variability of the monsoonal rainfall causes widespread droughts and floods, having a significant impact on the nation's food grain and economy" (Mohapatra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%